Exploring Cachexia: Severity, Functional Abilities, and Personal Experiences of Cancer Survivors through a Mixed-Methods Analysis - Deepika Ramalingam; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Duraikannu Anandhi; Divya Jayaraman; Shabana Ahamed; Venba Elangovan (Journal of Pharmacy and Bioallied Sciences)
Introduction: Cachexia, an involuntary weight loss and wasting of muscle, severely impairs the quality of life and treatment outcomes of survivors after cancer. Objectives: The study opted for this mixed-method design to assess cachexia severity; functional impacts of cachexia; and lived experiences among survivors with the condition. Methods: The cross-sectional study carried out at a tertiary care center in Chennai was based on the scores of 60 survivors of cancer, evaluated using the Cachexia Severity Score and Functional Assessment of Anorexia/Cachexia Therapy Scale, along with semi-structured interviews for six participants. Results: The study found a significant negative correlation between cachexia severity and functional ability (r = −0.32, P = 0.01). Cachexia severity (mean: 81.65) and functional ability (mean: 7.10) indicated significant functional impairment. Qualitative interviews highlighted emotional and physical challenges, with family support and religious beliefs as coping mechanisms, emphasizing the need for holistic care. Conclusion: Addressing cachexia therefore requires integrating physical rehabilitation, mental health support, and lifestyle adjustments to improve survivors’ quality of life and mitigate its multidimensional impact.